ANALISIS BIBLIOMETRIK: PERKEMBANGAN PENELITIAN ETNOMATEMATIKA DI SEKOLAH DASAR (2008-2023) - Nisaul Hikmiah, Alien; Mariana, Neni; Wiryanto, Wiryanto (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
The importance of bridging mathematics learning with everyday life around students is called ethnomathematics. The aim of this research is to look at ethnomathematics research trends, examine how to classify ethnomathematics, and review opportunities for ethnomathematics topics in elementary schools to become future research trends. This research data uses the Scopus database with VOSviewer. Data obtained by Scopus with the keywords